An Insight of Herbal Drugs and their Pharmaceutical Formulations Reported to have Hepatoprotective Activity - Mujahid, Md.; Usmani, Afreen; Akhlaqur Rahman, Md.; Azizur Rahman, Md. (Current Traditional Medicine, 2018)
Background: Medicinal plants play an important role in the world's human healthcare system including folk practices as well as Ayurveda, Unani and Siddha. Approximately, 80% of the world's human population relies on the usage of traditional medicine which is primarily based on plant-derived drugs. Liver is the most important organ for the detoxification of various toxins and disposition of the endogenous substances. It is always exposed to the toxins and chemotherapeutic agents that lead to hepatotoxicity. Herbal drugs and their pharmaceutical formulations have been used in the treatment of liver diseases and hepatotoxicity for a long time. Aims: The present review is aimed at compiling data on promising medicinal plants that have been tested in hepatotoxicity models using the modern scientific system. Materials and Methods: Literature surveys on scientific national and international journals, books as well as electronic resources were performed. Results: It showed several herbal drugs and their pharmaceutical formulations that have hepatoprotective activity. The herbal medicines mentioned were of an enormous value. Conclusion: This reported insight of herbal drugs and their pharmaceutical formulations will definitely be helpful to the future researchers and the practitioners while deciding and choosing an effective drug for the treatment of liver diseases and hepatotoxicity.
Keywords: Ayurveda